Post-functionalization of drug-loaded nanoparticles prepared by polymerization-induced self-assembly (PISA) with mitochondria targeting ligands - Noy, Janina-Miriam; Chen, Fan; Stenzel, Martina (Beilstein Journal of Organic Chemistry, 2021)
Herein, the postfunctionalization of different non-fouling PISA particles, prepared from either poly(oligo ethylene glycol methyl ether methacrylate) (pPEGMA) and the anticancer drug PENAO (4-(N-(S-penicillaminylacetyl)amino)phenylarsenonous acid) or zwitterionic 2-methacryloyloxyethyl phosphorylcholine (MPC) and PENAO were reported. Both PISA particles were reacted with triphenylphosphonium (TPP) as mitochondria targeting units in order to evaluate the changes in cellular uptake or the toxicity of the conjugated arsenic drug. Attachment of TPP onto the PISA particles however was found not to enhance the mitochondrial accumulation, but it did influence overall the biological activity of pMPC-based particles in 2D and 3D cultured sarcoma SW982 cells. When TPP was conjugated to the pMPC PISA particles more cellular uptake as well as better spheroid penetration were observed, while TPP on PEG-based PISA had only little effect. It was hypothesized that TPP on the micelle surface may not be accessible enough to allow mitochondria targeting, but more structural investigations are required to elucidate this.
Keywords: micelle; mitochondria; phosphorylcholine; PISA; polymerization-induced self-assembly

(untitled) - Fulda, S.; Galluzzi, L.; Kroemer, G. (Nat. Rev. Drug Discovery, 2010)

(untitled) - Dilda, P. J.; Decollogne, S.; Weerakoon, L.; Norris, M. D.; Haber, M.; Allen, J. D.; Hogg, P. J. (J. Med. Chem., 2009)

(untitled) - Dilda, P. J.; Hogg, P. J. (Cancer Treat. Rev., 2007)

(untitled) - Decollogne, S.; Joshi, S.; Chung, S. A.; Luk, P. P.; Yeo, R. X.; Nixdorf, S.; Fedier, A.; Heinzelmann-Schwarz, V.; Hogg, P. J.; Dilda, P. J. (Gynecol. Oncol., 2015)

(untitled) - Park, D.; Chiu, J.; Perrone, G. G.; Dilda, P. J.; Hogg, P. J. (Cancer Cell Int., 2012)

(untitled) - Kitchin, K. T.; Wallace, K. (J. Inorg. Biochem., 2008)

(untitled) - Kitchin, K. T.; Wallace, K. (Toxicol. Appl. Pharmacol., 2005)

(untitled) - Zhang, X.; Yang, F.; Shim, J.-Y.; Kirk, K. L.; Anderson, D. E.; Chen, X. (Cancer Lett., 2007)

(untitled) - Yan, X.; Li, J.; Liu, Q.; Peng, H.; Popowich, A.; Wang, Z.; Li, X.-F.; Le, X. C. (Angew. Chem., Int. Ed., 2016)

(untitled) - Zhang, X.; Cornelis, R.; De Kimpe, J.; Mees, L.; Lameire, N. (Clin. Chem., 1998)

(untitled) - Tanaka, J.; Davis, T. P.; Wilson, P. (Macromol. Rapid Commun., 2018)

(untitled) - Akhtar, A.; Wang, S. X.; Ghali, L.; Bell, C.; Wen, X. (J. Biomed. Res., 2017)

(untitled) - Qin, J.; Gong, N.; Liao, Z.; Zhang, S.; Timashev, P.; Huo, S.; Liang, X.-J. (Nanoscale, 2021)

(untitled) - Liew, S. S.; Qin, X.; Zhou, J.; Li, L.; Huang, W.; Yao, S. Q. (Angew. Chem., Int. Ed., 2021)

(untitled) - Cho, D. Y.; Cho, H.; Kwon, K.; Yu, M.; Lee, E.; Huh, K. M.; Lee, D. H.; Kang, H. C. (Adv. Funct. Mater., 2015)

(untitled) - Qu, Q.; Ma, X.; Zhao, Y. (Nanoscale, 2015)

(untitled) - Weissig, V.; Lizano, C.; Torchilin, V. P. (J. Liposome Res., 1998)

(untitled) - Weissig, V. (Pharm. Res., 2011)

(untitled) - Di, X.; Wang, D.; Zhou, J.; Zhang, L.; Stenzel, M. H.; Su, Q. P.; Jin, D. (Nano Lett., 2021)

(untitled) - Wang, Z.; Guo, W.; Kuang, X.; Hou, S.; Liu, H. (Asian J. Pharm. Sci. (Amsterdam, Neth.), 2017)

(untitled) - Sharma, A.; Soliman, G. M.; Al-Hajaj, N.; Sharma, R.; Maysinger, D.; Kakkar, A. (Biomacromolecules, 2012)

(untitled) - Marrache, S.; Dhar, S. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Yue, C.; Yang, Y.; Zhang, C.; Alfranca, G.; Cheng, S.; Ma, L.; Liu, Y.; Zhi, X.; Ni, J.; Jiang, W.; Song, J.; de la Fuente, J. M.; et al. (Theranostics, 2016)

(untitled) - Hou, J.; Yu, X.; Shen, Y.; Shi, Y.; Su, C.; Zhao, L. (Nanoscale Res. Lett., 2017)

(untitled) - Khatun, Z.; Choi, Y. S.; Kim, Y. G.; Yoon, K.; Nurunnabi, M.; Li, L.; Lee, E.; Kang, H. C.; Huh, K. M. (Biomacromolecules, 2017)

(untitled) - Blaikie, F. H.; Brown, S. E.; Samuelsson, L. M.; Brand, M. D.; Smith, R. A. J.; Murphy, M. P. (Biosci. Rep., 2006)

(untitled) - Neuzil, J.; Dyason, J. C.; Freeman, R.; Dong, L.-F.; Prochazka, L.; Wang, X.-F.; Scheffler, I.; Ralph, S. J. (J. Bioenerg. Biomembr., 2007)

(untitled) - Noy, J.-M.; Cao, C.; Stenzel, M. (ACS Macro Lett., 2019)

(untitled) - Noy, J.-M.; Lu, H.; Hogg, P. J.; Yang, J.-L.; Stenzel, M. (Bioconjugate Chem., 2018)

(untitled) - Zhang, Q.; Vakili, M. R.; Li, X.-F.; Lavasanifar, A.; Le, X. C. (Biomaterials, 2014)

(untitled) - Zhang, Q.; Vakili, M. R.; Li, X.-F.; Lavasanifar, A.; Le, X. C. (Mol. Pharmaceutics, 2016)

(untitled) - Tanaka, J.; Moriceau, G.; Cook, A.; Kerr, A.; Zhang, J.; Peltier, R.; Perrier, S.; Davis, T. P.; Wilson, P. (Macromolecules, 2019)

(untitled) - Karagoz, B.; Boyer, C.; Davis, T. P. (Macromol. Rapid Commun., 2014)

(untitled) - Zhang, W.-J.; Hong, C.-Y.; Pan, C.-Y. (Macromol. Rapid Commun., 2019)

(untitled) - Qiu, L.; Xu, C.-R.; Zhong, F.; Hong, C.-Y.; Pan, C.-Y. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Karagoz, B.; Esser, L.; Duong, H. T.; Basuki, J. S.; Boyer, C.; Davis, T. P. (Polym. Chem., 2014)

(untitled) - Phan, H.; Taresco, V.; Penelle, J.; Couturaud, B. (Biomater. Sci., 2021)

(untitled) - Zhang, W.-J.; Hong, C.-Y.; Pan, C.-Y. (Biomacromolecules, 2016)

(untitled) - Wright, D. B.; Proetto, M. T.; Touve, M. A.; Gianneschi, N. C. (Polym. Chem., 2019)

(untitled) - Su, G.; Jiang, H.; Xu, B.; Yu, Y.; Chen, X. (Mol. Pharmaceutics, 2018)

(untitled) - Suk, J. S.; Xu, Q.; Kim, N.; Hanes, J.; Ensign, L. M. (Adv. Drug Delivery Rev., 2016)

(untitled) - Noy, J.-M.; Chen, F.; Akhter, D. T.; Houston, Z. H.; Fletcher, N. L.; Thurecht, K. J.; Stenzel, M. H. (Biomacromolecules, 2020)

(untitled) - Cao, C.; Chen, F.; Garvey, C. J.; Stenzel, M. H. (ACS Appl. Mater. Interfaces, 2020)

(untitled) - Leng, C.; Hung, H.-C.; Sun, S.; Wang, D.; Li, Y.; Jiang, S.; Chen, Z. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Settanni, G.; Schäfer, T.; Muhl, C.; Barz, M.; Schmid, F. (Comput. Struct. Biotechnol. J., 2018)

(untitled) - Honary, S.; Zahir, F. (Trop. J. Pharm. Res., 2013)

(untitled) - Lu, H.; Stenzel, M. H. (Small, 2018)

(untitled) - Mirshafiee, V.; Mahmoudi, M.; Lou, K.; Cheng, J.; Kraft, M. L. (Chem. Commun., 2013)

(untitled) - Reineke, J. (J. Controlled Release, 2018)

(untitled) - Dai, Q.; Walkey, C.; Chan, W. C. W. (Angew. Chem., Int. Ed., 2014)

(untitled) - Lu, M. X.; Khine, Y. Y.; Chen, F.; Cao, C.; Garvey, C. J.; Lu, H. X.; Stenzel, M. H. (Biomacromolecules, 2019)

(untitled) - Cao, C.; Zhao, J. C.; Lu, M. X.; Garvey, C. J.; Stenzel, M. H. (Biomacromolecules, 2019)

(untitled) - Stenzel, M. H. (Angew. Chem., Int. Ed., 2021)